Multiobjective stochastic scheduling of upstream operations in a sustainable sugarcane supply chain. (10th December 2020) - Morales Chavez, Marcela María; Sarache, William; Costa, Yasel; Soto, José
Abstract: A typical supply chain is composed of three main echelons: upstream, mid-stream and downstream. In the case of sugarcane, the upstream echelon includes several activities, such as growth, harvest, and transportation to mills. As multiple authors have pointed out the importance of proper scheduling for these supply chain echelons, as well as the need to develop more realistic optimization models, the present investigation proposes a multi-objective stochastic optimization model for upstream scheduling, with a sustainable approach. The model involves robust planning for harvest, maintenance, and transportation. It also sets the operations schedule for workforce, agricultural machinery, and vehicles. In contrast to previous contributions regarding sugarcane supply chain optimization, the effect of sugarcane yield uncertainty on harvest scheduling and resource allocation is incorporated. Further, upstream operations performance was analyzed, using a sustainable approach. A real-life cases study is examined in this paper. We used compromise programing approach to seek the best trade-off with respect to the utilization of different harvesting methods. Linked to the above, our computational results show that the sugarcane harvesting should be mostly carry out using mechanical method. Through the use of harvesting machinery, the total operation costs and negative environmental is significantly smaller compared to the manual harvesting. Results also show that social goals (job creation) is positively impact by greater utilization of manual harvesting. Most importantly, our computational outcomes are useable to find a proper balance between mechanical and manual harvesting; achieving at the same time, the best possible performance values for the studied sustainable goals. Highlights: An optimization model to schedule a sustainable sugarcane supply chain is presented. The model involves robust planning for harvest, maintenance, and transportation. The effect of sugarcane yield uncertainty on scheduling is analyzed. The impact of harvesting and transport decisions on sustainability was assessed.